KONSELING ISLAM DENGAN DZIKIR TAREKAT QADIRIYAH NAQSABANDIYAH: MENGATASI KEGELISAHAN JIWA DAN BATHIN - Maidatus Sholihah; Muhammad Anas Maarif; Moh. Syahru Romadhan (Fakultas Agama Islam Universitas Wiralodra, 2021)
This article aims to describe and analyze Islamic counseling based on dzikir Tareeqa Qadiriyah Naqsabandiyah (TQN). TQN dhikr is a way to reduce inner restlessness and anxiety. This article uses the literature review method by elaborating books, scientific papers, and journals that are relevant to TQN dhikr-based Islamic counseling. This article uses content analysis techniques in several journals and books related to TQN dhikr and Islamic counseling. The results of this study are: 1) Dzikir TQN is able to play a role in reducing negative attitudes that exist in individuals (prevention). 2) TQN dhikr is able to heal individuals from disgraceful attitudes and actions (curative). 3) The counselor acts like a murshid who is professionally able to detect client problems. 4) TQN dhikr is one way to overcome the problems of life kline so, it is possible that there are other ways that a counselor can do to solve client problems.